Analysis of the antioxidant potential of brown seaweed Turbinaria decurrens from the Sinar Bahagia Coastal Waters, Simeulue Island, Indonesia: Analisis potensi antioksidan rumput laut cokelat Turbinaria decurrens dari Perairan Pesisir Sinar Bahagia Kepulauan Simeulue, Indonesia - Gazali, Mohamad; Zulafrizal, Zulafrizal; Zuriat, Zuriat; Saidin, Jasnizat; Nurjanah, Nurjanah; Syafitri, Rina; Setiyana, Rusma (Jurnal Pengolahan Hasil Perikanan Indonesia, 2026)
Turbinaria decurrens, a brown seaweed native to the coastal waters of Sinar Bahagia, Simeulue Island, Aceh, has antioxidant properties. This study aimed to evaluate the antioxidant potential of brown seaweed T. decurrens extracts. The research method includes phytochemicals, total phenol content and antioxidant activity assay with DPPH method with different solvents included methanol, ethyl acetate, and n-hexane solvents Phytochemical screening demonstrated the existence of flavonoids, saponins, phenolics, and steroids in all extracts, indicating a substantial repository of secondary metabolites. The DPPH radical scavenging experiment was used to measure the antioxidant activity. The methanol extract showed the strongest activity (IC₅₀ = 22.1±0.47 mg/mL), followed by ethyl acetate (IC₅₀ = 36.7±2.52 mg/mL) and n-hexane (IC₅₀ = 46.68±1.79 mg/mL). The total phenolic content was highest in the methanol extract (2.43 mg GAE/g), followed by ethyl acetate (1.50 mg GAE/g) and n-hexane (0.73 mg GAE/g). A strong positive correlation (R2 = 0.95) between total phenol content and antioxidant activity indicates that phenolic compounds are the dominant contributors to the radical scavenging capacity of T. decurrens extract. T. decurrens extract with methanol as the solvent showed a relatively higher phenolic content and antioxidant potential than those of other solvents. In conclusion, T. decurrens extracts demonstrated phenolic content and antioxidant potential, with methanol yielding a comparatively higher total phenolic content and activity among the tested solvents. These observations suggest opportunities for its use in nutraceutical or functional food applications, pending further validation studies. Future studies should explore specific phenolic isolation, in vivo evaluations, and broader solvent optimizations.